Peningkatan Kualitas Pelayanan Kereta Komuter Berdasarkan Persepsi Pengguna Dengan Menggunakan Metode ServQual dan Zone of Tolerance: Studi Kasus Tanah Abang DKI Jakarta - Fredy Jhon philip Sitorus; Fresly Verliando Montana (WIDYAKALA JOURNAL : JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2023)
This study focuses on the extent to which commuter train users are satisfied with the services provided by service providers. The purpose of this study was to find out the level of satisfaction of commuter train users while at the same time providing service improvement efforts to be used as evaluation material for service providers. The method used is Service Quality and Zone of tolerance with the help of a questionnaire that is prepared according to the five dimensions of service quality and refers to PM. 48 of 2015. The data collection method was carried out by distributing questionnaires containing 23 statement attributes to respondents, respondents in this study were commuter train users who had an age range of 17-50 years and used commuter trains at least four times a week. The data analysis method uses gap 5 ServQual and Zone of tolerance calculation. The results showed that the value of the ServQual gap in all statement attributes in the questionnaire was negative, then there were several statement attributes that were still below the tolerance zone and there were requests from potential users about the queue time when entering the station. The conclusion of this study is that commuter train users are still not satisfied with the services provided and there are priority service improvements that must be considered by PT. KCI.